2017
DOI: 10.18203/2394-6040.ijcmph20171766
|View full text |Cite
|
Sign up to set email alerts
|

A study on nutritional status of adolescent girls of Dongria Kondh tribe

Abstract: Background: Nutritional status of adolescent girls are different from the younger children and older adults. In the tribal population they are more neglected in comparison to boys because of limited resources and health care facilities. In the present study we have done assessment of nutritional status of adolescent girls in the Dongria Kondh tribe in Odisha. Methods: Dongria Kondh’ residing in Rayagada district of Odisha, having its maximum concentration was studied. Bissam Cuttack block was selected randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…The overall Mean ± SD of anaemia was 9.40 ± 1.86 g/dl. Similarly, Shrinivasa et al, (2014), Siddiqui et al, (2016) and Nanda and Dhar (2017) had reported higher percentage of anaemia prevalence in the reproductive age group. The prevalence of anaemia among the study tribal women had a higher percent in comparison to other tribes in India reported by Choudhary and Dashora (2015), Dabral and Kothiyal (2016), and Kaur and Kaur (2011).…”
Section: Anaemiamentioning
confidence: 79%
See 1 more Smart Citation
“…The overall Mean ± SD of anaemia was 9.40 ± 1.86 g/dl. Similarly, Shrinivasa et al, (2014), Siddiqui et al, (2016) and Nanda and Dhar (2017) had reported higher percentage of anaemia prevalence in the reproductive age group. The prevalence of anaemia among the study tribal women had a higher percent in comparison to other tribes in India reported by Choudhary and Dashora (2015), Dabral and Kothiyal (2016), and Kaur and Kaur (2011).…”
Section: Anaemiamentioning
confidence: 79%
“…Food habits effect nutritional status therefore is necessary to assess the tribal food habits because a particular tribe food habits differ to another tribe and also from one region to another (Joshi and Singh, 2015). The common types of food consumed are rice, ragi and seasonal fruits and non-vegetarian (Nanda and Dhar, 2017). Nutritional knowledge of the tribal adult women was unsatisfactory and they need in-depth nutrition education and intervention programmes for their holistic development (Devi and Sindhuja, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The respondents averaged 20.0 ± 1.32 years, with an age range of 18-22 years. In the study, the respondents' age was included in the late adolescent category (ages [18][19][20][21][22][23][24][25]. The new youth is not a time of children or adults but a start to growth [16].…”
Section: Resultsmentioning
confidence: 99%
“…Functional nutritional status is vital for maintaining body health. Nutritional counseling needs to be provided, especially in women, to make their lives more productive, safer, and prosperous [18]. Therefore, given that the respondent is the athlete who is required to be in shape, it is essential to give directions concerning a nutritional condition.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…However, in case of consumption of fat, it is above the normative requirement. Mittal (2013), Rao and Sugunan et al, (2006), Kaur andKaur (2011), Nanda andDhar (2017) and Wani and Jan (2016) had also reported the dietary intake of the tribal women lower than the RDA.…”
Section: Dietary Intake (24 Hours Recall Method)mentioning
confidence: 99%